1999
DOI: 10.1038/5985
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of ovarian lifespan into advanced chronological age by Bax-deficiency

Abstract: Female mammals are endowed with a finite number of oocytes at birth, each enclosed by a single layer of somatic (granulosa) cells in a primordial follicle. The fate of most follicles is atretic degeneration, a process that culminates in near exhaustion of the oocyte reserve at approximately the fifth decade of life in women, leading to menopause. Apoptosis has a fundamental role in follicular atresia, and recent studies have shown that Bax, which is expressed in both granulosa cells and oocytes, may be central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
257
4
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(284 citation statements)
references
References 13 publications
16
257
4
7
Order By: Relevance
“…First, it is important to re-emphasize the wealth of data already available identifying Bax as a key proapoptotic constituent of the female germ cell death program under diverse conditions. 7,[13][14][15] With this in mind, along with recent data reporting that oocyte production in adult females, like sperm production in adult males, is sustained by germline stem cells, 17,18 we have begun to examine whether the 'nomenopause' ovarian phenotype of Bax-deficient female mice is due not only to a reduced incidence of oocyte death, as reported earlier, 14 but also to failed apoptotic deletion of germline stem cells in aging females. Whereas extensive experimentation is needed, and currently underway, to test the validity of this theory, as yet unpublished work using a different proapoptotic gene mutant mouse line has revealed a marked expansion of the oocyte-containing follicle pool in adult females that, unlike the Bax-deficient mouse, cannot be explained even in part by a reduced incidence of oocyte death.…”
Section: Bax: a Master Regulator Of Apoptosis In The Ovarymentioning
confidence: 85%
See 1 more Smart Citation
“…First, it is important to re-emphasize the wealth of data already available identifying Bax as a key proapoptotic constituent of the female germ cell death program under diverse conditions. 7,[13][14][15] With this in mind, along with recent data reporting that oocyte production in adult females, like sperm production in adult males, is sustained by germline stem cells, 17,18 we have begun to examine whether the 'nomenopause' ovarian phenotype of Bax-deficient female mice is due not only to a reduced incidence of oocyte death, as reported earlier, 14 but also to failed apoptotic deletion of germline stem cells in aging females. Whereas extensive experimentation is needed, and currently underway, to test the validity of this theory, as yet unpublished work using a different proapoptotic gene mutant mouse line has revealed a marked expansion of the oocyte-containing follicle pool in adult females that, unlike the Bax-deficient mouse, cannot be explained even in part by a reduced incidence of oocyte death.…”
Section: Bax: a Master Regulator Of Apoptosis In The Ovarymentioning
confidence: 85%
“…6 Working with Stan, we then documented in a series of papers the requirement for Bax in mediating death of the female germline as well, under both normal and pathological situations. [13][14][15] Among the most striking of these was our finding that the loss of Bax in female mice sustained ovarian function well into advanced chronological age, 14 thereby eliminating the mouse equivalent of the menopause. Although the initial interpretation from this work was that Bax deficiency conveyed this effect by suppressing the rate at which oocytes and follicles are lost from the ovaries in adulthood, we have Cell Death and Differentiation (2006) 13,[1296][1297][1298] now begun to re-visit this model based on very new data discussed below.…”
Section: Bax: a Master Regulator Of Apoptosis In The Ovarymentioning
confidence: 97%
“…Bcl-2 was the first cell survival factor discovered in mammals, as it functions as an anti-apoptotic gene and is a key factor in regulating both physiological and pathological apoptosis. When the ratio of Bcl-2/Bax is increased, the dimer facilitates cell survival; however, when the ratio is decreased, the dimer facilitates apoptosis [17,18] . The present study showed no expression of the Bcl-2 protein, but did show significant expression of the Bax protein in the DOX group, as well as the existence of minor Bcl-2 proteins in light color and abundant Bax proteins in dark color, indicating a close association between the expression of Bcl-2 and Bax proteins and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Though ovarian phenotypes have not been reported, a deficiency of Bid caused resistance to apoptosis mediated by cell death ligand and receptor in mice hepatocytes [29]. Moreover, a deficiency of Bax disrupted granulosa cell apoptosis (aberrant atresia) and affected rates of atresia among primordial and primary follicles in mice [30,31]. Considering these reports, BID and BAX are necessary for apoptotic signal transduction in granulosa cells of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%